Prototipo del Sistema de Computación Embebido para Investigación a Gran Altura (ACAE) - Wigoda-Kaver, Yoel (Instituto Tecnológico de Costa Rica, 2011)
The Central American Association of Aeronautics and Space (ACAE) aims to capture the attention of various entities through innovative projects based on high-end technology, in order to achieve in the future the formation of the Chamber of Aerospace Industries in Central America. ACAE then proposed a first project, whose objectives revolve around the fulfillment of this goal called "DAEDALUS", which consist in the development of a modular platform design for scientific research that can take physical measurements at high altitudes. The development tasks of the project were divided and assigned to various engineering teams based on technical emphasis. The computing functions done by platform, are performed by the electronic system aboard called SCEIGA, whose design and implementation are fully covered in this document. The SCEIGA is a low-power mobile computing system that specializes in data acquisition in hostile environments. Its use in the DAEDALUS platform will allow video and photo capture of the earth curvature and also to capture atmospheric measurements. Such measurements can be observed in real time from anywhere in the world through Internet access, because the system is able to publish its set of measurements automatically through the social network Twitter. The system's design foresaw the physical limitations that threaten the proper functioning of electronic devices in hostile environments such as low temperatures, low atmospheric pressure and electromagnetic interference. Based on the design, a functional SCEIGA prototype was built using development boards. The prototype was fully tested in order to verify that the design objectives were successfully accomplished. Finally, a series of technical recommendations are presented. This recommendations could be taken in account for development in future stages of this project or in similar projects.
"Proyecto DAEDALUS"
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2011.
Keywords: Sensores; Operaciones; Temperatura; Electricidad; Conexiones; Humedad; Topología